A Look at the History of Cultural Centers (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article presents sources related to the history of cultural centers in Uzbekistan. It discusses not only historical aspects but also the political processes involved in the formation of cultural centers. Definitions of the term club are examined. In addition, the article offers brief suggestions for the development of cultural centers. The article highlights the stages of development of cultural centers based on historical sources and contemporary legislation, while also emphasizing their social, educational, and cultural significance.